The Effect of Online Learning on Students’ English Learning Achievement - Nurohmat Nurohmat (Scripta : English Department Journal, 2020)
The Covid-19 pandemic has brought big changes in teaching and learning activities in the country. Learning activities have changed from face-toface to online teaching and learning. Studying online changes the learningexperience for many students. Rather than sitting in school and taking notes, students are taking advantage of online classes and other forms of online learning. Materials and Methods: Survey and interview. Interviews were conducted with the homeroom teacher. Survey of student scores in the semester before the Covid-19 pandemic and during the pandemic. Results: Based on the results obtained, on-line learning has little effect on learning achievement. Online learning has several advantages and disadvantages over learning face-toface. Online learning offers a potentially better alternative if it is adapted to the situation and conditions of the students.